Deformation behaviour of 3D printed reinforced hydroxyapatite/gelatin bio-ceramics - Megalingam, Arumugampillai; Rajamony, Reji Kumar; Perumal, M. A.; Malliga, S. (Mahendra Publications, 2023)
This paper investigates the deformation behaviour of three-dimensional (3D) printed reinforced hydroxyapatite/gelatine bio-ceramics. The worldwide demand for organ replacement or tissue regeneration is increasing steadily. The advancements in tissue engineering and regenerative medicine have made it possible to regenerate such damaged organs or tissues into functional organs or tissues with the help of 3D bioprinting. In this technology, 3D bioprinting is a rapid prototyping technique that excels at producing quality products using complex shapes and materials that are difficult to handle with precise parameters. Bio-ceramic-based composites are increasingly preferred for bone tissue preparation due to their desirable osteogenic properties. Although the bioactivity and low toxicity of hydroxyapatite are considered favourable, their poor mechanical properties, low fracture toughness, and tensile strength are of concern. The use of graphene oxide (GO) as reinforcement, has the potential to improve the mechanical and biological properties of bio-ceramic composites. Cross-linking by genipin adds additional strength to the model. However, there is a lack of deformation behaviour defining mechanical properties in the literature. Thus, there is a lack of comprehensive understanding of such bio-ceramics. The study is expected to contribute to ongoing research on biocompatible materials for the development of patient-specific implants and scaffolds by closely studying their deformation behaviour. It presents a recommendation for the use of GO in the formulation of bio-ceramic composites and its cross-linking by genipin to improve mechanical properties.